Azerbaijan Republic : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2004)
This paper examines the progress report on Azerbaijan Republic's Poverty Reduction Strategy Paper. The share of the production and non-oil sector in GDP has increased. The shares of industry, construction, wholesale, and retail and service sectors increased, while the shares of agriculture transport and communication, hotel, restaurant, social and informal service sectors and net taxes from goods and imports decreased. Agricultural reforms lead to a real growth rate of 6.4 percent in 2002 and 5.6 percent in 2003. The share of crop production in agricultural production has been 60 percent and of livestock production 40 percent in the reported period.